2019
DOI: 10.1039/c9mt00184k
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and proteomic changes induced by growth inhibitory concentrations of copper in the biofilm-forming marine bacteriumPseudoalteromonas lipolytica

Abstract: Copper exposure in P. lipolytica TC8 revealed changes in cell membrane lipid composition and in copper cell homeostasis protein regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…Copper induces biofilm formation in the wild type but not the cpxR and zapD mutants. Copper has been reported to trigger CpxAR-mediated gene expression (38,39) and to be associated with biofilm formation (40). We found that CpxR regulated the expression of the zapABCD operon (Fig.…”
Section: Figmentioning
confidence: 60%
See 1 more Smart Citation
“…Copper induces biofilm formation in the wild type but not the cpxR and zapD mutants. Copper has been reported to trigger CpxAR-mediated gene expression (38,39) and to be associated with biofilm formation (40). We found that CpxR regulated the expression of the zapABCD operon (Fig.…”
Section: Figmentioning
confidence: 60%
“…In addition, a number of studies implicate copper stress genes in envelope functions, including biofilm formation (14,55). Copper exposure seems to induce changes in bacterial membrane composition (40), and the biofilm matrix polysaccharides were shown to be able to attenuate the reactive oxygen species (ROS) generated by copper dried, cells in each well were stained with crystal violet (1%). The crystal violet-stained biofilms were extracted with a mixture of acetone and 95% alcohol (1:4).…”
Section: Discussionmentioning
confidence: 99%
“…This study only revealed the proteome of E. huxleyi, whereas the metabolome was not accessed, and thus, many critical features relating to metabolites in this species remained unknown. Several studies have performed an integrated metabolomics-proteomics, which could show a better landscape of the marine plankton [81,82]. Integrating "-omics" studies (e.g., genomics, proteomics, transcriptomics, metabolomics, lipidomics, and glycomics) will enable the investigation of the impacts of ecological interactions on organism physiology as well as evaluation of physiological and biochemical properties relating to human health for future applications [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of untargeted metabolomics is to capture as many metabolites as possible in the samples under comparison without any bias and is usually implemented as a hypothesis-generating approach. Monitoring of global metabolic profiles occurring under different physiological states (planktonic vs biofilm) (111,112) or drug-treatment/stress conditions (113) would provide an overview of the changes occurring within a system and can provide key insights into the regulatory pathways mediating bacterial lifestyle switch, drug resistance, or persister cell formation. However, there are many technical difficulties associated with untargeted metabolomics, which may lead to bias in analysis.…”
Section: Untargeted Metabolomicsmentioning
confidence: 99%
“…Studies by Favre et al (113) and Booth et al (153) investigate the differential response of planktonic vs biofilm cells in response to copper exposure in Pseudoalteromonas lipolytica and P. flourescens, respectively. Some studies have addressed very specific questions using metabolomics.…”
Section: Current Applications Of Biofilm Metabolomicsmentioning
confidence: 99%